THE ACETONE EXTRACT FROM DRIED MATERIALS OF COMMELINA BENGHALESIS HAVE ENHANCED EFFECT ON THE CANCEROUS JURKATS T-CELLS - Mokgotho, M. P.; Masoko, P.; Mbazima, V. G.; Sibuyi, N.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cancer is one of the major human diseases and causes considerable suffering and economic loss worldwide. Development of safe products for the prevention and treatment of all human cancers is needed. Because of plant safety, there has been growing interest in the beneficial health effects of medicinal plants, with the presence of phenolic antioxidants believed to have the protective mechanisms. Plants have been demonstrated to be a very viable source of clinically relevant anticancer compounds. Commelina benghalesis is one of the commonly used medicinal plants in China, Ethopia and in South Africa. The objective of the study was to examine the antioxidant activity, its phenolic content and the effect it might have on the Jurkats T-cell line using the fresh and the dried extracts. The dried and the fresh stems of C. benghalensis were extracted with acetone using a soxhlet method and concentrated to dryness with rotary evaporator. The total phenolic content of the extracts was determined by Folin–Ciocalteu method and antioxidant activity was assayed using DPPH method. The total phenolic contents and antioxidant activity of the extracts as tannic acid equivalents were found to be highest in fresh extract. Trypan blue exclusion dye results demonstrated that the dried acetone extracts had inhibited cell proliferation more. The inhibition was in a dose-dependent manner. Acknowledgements: NRF and University of Limpopo Research office